2019
DOI: 10.1111/tid.13132
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of Kaposi sarcoma masquerading as cystitis in a kidney transplant recipient

Abstract: Human Herpes Virus-8 (HHV-8) may reactivate in immunocompromised patients including recipients of solid organ transplants. Reactivation of HHV-8 may result in Kaposi sarcoma (KS). KS typically occurs with dermatologic involvement but can affect virtually any other organ; most commonly the gastrointestinal tract. We present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Renal involvement of KS in AIDS patients is not commonly observed at imaging; rather, it is more commonly found during autopsy due to its microscopic nature [48]. As with GI KS, associated lymphadenopathy tends to be hypervascular and manifests as enhancing nodes [49]. Differential considerations include Castleman's disease, which can coexist with KS.…”
Section: Genitourinary Kaposi Sarcomamentioning
confidence: 99%
“…Renal involvement of KS in AIDS patients is not commonly observed at imaging; rather, it is more commonly found during autopsy due to its microscopic nature [48]. As with GI KS, associated lymphadenopathy tends to be hypervascular and manifests as enhancing nodes [49]. Differential considerations include Castleman's disease, which can coexist with KS.…”
Section: Genitourinary Kaposi Sarcomamentioning
confidence: 99%
“…Details about the donors, induction therapy, and HHV‐8 testing were generally not reported. Imaging findings were non‐specific and included a focal mass, a thickened renal hilum and sinus, or diffuse heterogeneity on ultrasound, CT or MRI 12,36,39,40 . All of these imaging features have broad overlap between benign and malignant etiologies 36,39,41 .…”
Section: Discussionmentioning
confidence: 99%
“…It typically occurs with dermatologic involvement but recent case reports described cases of disseminated disease without typical skin involvement, which posed an important diagnostic challenge. Atypical localizations included tonsillar Kaposi sarcoma [17], bladder thickening and pelvic lymphadenopathy, penis, lower extremities and thoracic lymph nodes in kidney transplant recipients [18]; liver nodules and portal vein thrombosis in a paediatric liver recipient [12]. Moreover, in 2020, two autopsy-diagnosed cases in renal transplant recipients confirmed that different HHV-8-driven neoplasms could coexist in the same patient: intravascular lymphoma and synchronous Kaposi sarcoma [19].…”
Section: Human Herpesvirus 8-associated Disordersmentioning
confidence: 98%